New strategies for neuro protection in glaucoma - Xuejiao, Yang; Junwei, Yan (Frontiers in Cell and Developmental Biology, 2022)
Glaucoma is a progressive, irreversible loss of retinal ganglion cells (RGCs) and axons that results in characteristic optic atrophy and corresponding progressive visual field defect. The exact mechanisms underlying glaucomatous neuron loss are not clear. The main risk factor for glaucoma onset and development is high intraocular pressure (IOP), however traditional IOP-lowering therapies are often not sufficient to prevent degeneration of RGCs and the vision loss may progress, indicating the need for complementary neuroprotective therapy. This review summarizes the progress for neuro protection in glaucoma in recent 5 years, including modulation of neuroinflammation, gene and cell therapy, dietary supplementation, and sustained-release system.